2016
DOI: 10.3389/fpls.2016.00898
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Boron-Excess-Induced Alterations of Gene Profiles in Roots of Two Citrus Species Differing in Boron-Tolerance Revealed by cDNA-AFLP

Abstract: Boron (B) toxicity is observed in some citrus orchards in China. However, limited data are available on the molecular mechanisms of citrus B-toxicity and B-tolerance. Using cDNA-AFLP, we identified 20 up- and 52 down-regulated genes, and 44 up- and 66 down-regulated genes from excess B-treated Citrus sinensis and Citrus grandis roots, respectively, thereby demonstrating that gene expression profiles were more affected in the latter. In addition, phosphorus and total soluble protein concentrations were lowered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…We obtained two up-accumulated proteasomes (G6 and 13) and two up-accumulated ubiquitin-conjugating enzymes (G48 and 54) from B-toxic C. grandis roots, but only one up-accumulated proteasome (S9) from B-toxic C. sinensis (Tables 2 , 3 ), demonstrating that B-toxicity accelerated proteolysis, especially in the former. This agrees with our data that B-toxicity only decreased total soluble protein concentration in B-toxic C. grandis roots (Guo et al, 2016 ). B-toxicity-induced increase in protein degradation implies that misfolded and damaged proteins were increased in B-toxic C. sinensis and C. grandis roots, especially in the latter.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…We obtained two up-accumulated proteasomes (G6 and 13) and two up-accumulated ubiquitin-conjugating enzymes (G48 and 54) from B-toxic C. grandis roots, but only one up-accumulated proteasome (S9) from B-toxic C. sinensis (Tables 2 , 3 ), demonstrating that B-toxicity accelerated proteolysis, especially in the former. This agrees with our data that B-toxicity only decreased total soluble protein concentration in B-toxic C. grandis roots (Guo et al, 2016 ). B-toxicity-induced increase in protein degradation implies that misfolded and damaged proteins were increased in B-toxic C. sinensis and C. grandis roots, especially in the latter.…”
Section: Resultssupporting
confidence: 94%
“…In addition, the typical visible B-toxic symptom only occurred in B-toxic C. grandis leaves, but was not found in B-toxic C. sinensis leaves except for very few seedlings (Figure S1 ). Previous studies showed that B-toxicity only decreased the concentrations of phosphorus (P) and total soluble proteins in C. grandis roots (Guo et al, 2016 ). Based on these results, we concluded that C. sinensis had higher B-tolerance than C. grandis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations